2018
DOI: 10.1002/jmv.25191
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate genotypes of hepatitis C virus by the Abbott RealTime HCV Genotype II assay in Morocco. About eight cases resolved by a sequencing method

Abstract: The early detection and genotyping of the hepatitis C virus (HCV) are important in the management of this infection. The genotype is the major factor influencing treatment decisions. That's why it is necessary to use fast and accurate methods in its determination. This study reports, over a period of 3 years (from May 2012 to July 2015), the percentage of indeterminate genotypes by the Abbott RealTime HCV Genotype II test and their results using a sequencing technique. Of 309 samples of 309 patients tested, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recently, another study reported this finding, and this was explained by cross-reactivity or mixed infections. Sequencing the samples with undetermined genotypes might be a significant key to resolving the ambiguity regarding the undefined genotypes and identifying more subtypes [23]. Moreover, the cause of not identifying the specific genotypes could be due to other factors, including small sample quantity or more genotypes and subtypes that have not yet been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study reported this finding, and this was explained by cross-reactivity or mixed infections. Sequencing the samples with undetermined genotypes might be a significant key to resolving the ambiguity regarding the undefined genotypes and identifying more subtypes [23]. Moreover, the cause of not identifying the specific genotypes could be due to other factors, including small sample quantity or more genotypes and subtypes that have not yet been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…We used ART HCV assays (RealTime HCV and HCV Genotype II, Abbott Molecular, Abbott Park, IL, USA) to quantify HCV viral RNA load and genotyping. The assay detects genotypes 1, 2, 3, 4, 5, and 6, and subtypes 1a and 1b with genotype-specific fluorescent-labeled oligonucleotide probes [ 20 , 22 , 23 ]. An “indeterminate” result means a detectable HCV viral load without the ability to produce a genotype result.…”
Section: Methodsmentioning
confidence: 99%